2020
DOI: 10.1039/c9cp06678k
|View full text |Cite
|
Sign up to set email alerts
|

Microhydration of verbenone: how the chain of water molecules adapts its structure to the host molecule

Abstract: The microsolvation of verbenone (C10H14O)·(H2O)n (n = 1, 2, 3) was investigated in a supersonic expansion using a cavity-based Fourier transform microwave spectrometer, in the 2.8–14 GHz frequency range and by computational chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
3
14
0
Order By: Relevance
“…A similar arrangement was also observed for acenaphthene‐(H 2 O) 3 [22] and CH 2 F 2 ‐(H 2 O) 3 [23] . Interestingly, when complexing with β‐propiolactone, [24] camphor, [25] the glycoaldehyde dimer, [26] or verbenone, [27] the water trimer adopts a chain structure. In the formamide‐(H 2 O) 3 complex, all molecules, including formamide, are located almost in one plane closing a sequential cycle.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…A similar arrangement was also observed for acenaphthene‐(H 2 O) 3 [22] and CH 2 F 2 ‐(H 2 O) 3 [23] . Interestingly, when complexing with β‐propiolactone, [24] camphor, [25] the glycoaldehyde dimer, [26] or verbenone, [27] the water trimer adopts a chain structure. In the formamide‐(H 2 O) 3 complex, all molecules, including formamide, are located almost in one plane closing a sequential cycle.…”
Section: Introductionsupporting
confidence: 68%
“…The water trimer thus forms different configurations depending on the solute molecule that it interacts with, highlighting the crucial role of the interplay between the water–water and water–solute interactions. A comparison of these studies indicates that the water trimer prefers to form chains when it interacts with the solute molecule as a HB donor through a strong HB such as OH⋅⋅⋅O, otherwise it prefers the cyclic form [18, 21–28] . This naturally leads to the question: Which structure will the water trimer adopt when the solute molecule offers several different docking sites simultaneously?…”
Section: Introductionmentioning
confidence: 99%
“…Asimilar arrangement was also observed for acenaphthene-(H 2 O) 3 [22] and CH 2 F 2 -(H 2 O) 3 . [23] Interestingly,w hen complexing with b-propiolactone, [24] camphor, [25] the glycoaldehyde dimer, [26] or verbenone, [27] the water trimer adopts ac hain structure.I nt he formamide-(H 2 O) 3 complex, all molecules,i ncluding formamide,a re located almost in one plane closing as equential cycle.Itwas shown that formamide can act as asubstitute of two water molecules,a nd the formamide-(H 2 O) 3 complex mimics the overall structure of the cyclic water pentamer. [28] Thewater trimer thus forms different configurations depending on the solute molecule that it interacts with, highlighting the crucial role of the interplay between the water-water and water-solute interactions.Acomparison of these studies indicates that the water trimer prefers to form chains when it interacts with the solute molecule as aH Bd onor through as trong HB such as OH•••O,o therwise it prefers the cyclic form.…”
Section: Introductionmentioning
confidence: 99%
“…[28] Thewater trimer thus forms different configurations depending on the solute molecule that it interacts with, highlighting the crucial role of the interplay between the water-water and water-solute interactions.Acomparison of these studies indicates that the water trimer prefers to form chains when it interacts with the solute molecule as aH Bd onor through as trong HB such as OH•••O,o therwise it prefers the cyclic form. [18,[21][22][23][24][25][26][27][28] This naturally leads to the question:W hich structure will the water trimer adopt when the solute molecule offers several different docking sites simultaneously?…”
Section: Introductionmentioning
confidence: 99%
“…Water complexes can also modify photochemical reactions and the absorption of solar radiation . All the above have led to an increasing interest in water complexes of VOCs and their oxidized products. …”
mentioning
confidence: 99%